Navigating Leadership Succession and Regeneration in a Private Christian School: A Case Study - Maharani, Laksmi; Winardi, Yonathan (Diligentia: Journal of Theology and Christian Education, 2025)
This study explores the complexity of leadership succession and regeneration in a private Christian school in West Jakarta and possible ways to navigate the challenges, as the school has experienced a high turnover rate in its leadership in the past five years. Using a qualitative case study approach, this research collected the data through in-depth interviews, observations, and document analysis. Principals as well as heads of schools participated and the research results revealed a discrepancy between the educational philosophy of Christian schools and the practices of leadership succession and regeneration, lacking a specific system or strategy. Moreover, there is no formal succession and inadequate spiritual mentoring for the school leader candidates. Therefore, considering that succession is also a spiritual mandate, this study offers a contextual and values-based pathway for leadership regeneration, which includes early-stage talent mapping, structured leadership development, spiritual mentorship, and alignment with the school’s Christian philosophy to ensure the continuity of biblically grounded leadership.